Induction of humoral and cellular immune responses against the HIV-1 envelope protein using γ-retroviral virus-like particles - Purcell Damian FJ; Center Robert J; Pedersen Finn S; Bahrami Shervin; Melchjorsen Jesper; Wheatley Adam; Kirkegaard Tea; Ostergaard Lars; Duch Mogens; Tolstrup Martin (Virology Journal, 2011)
Abstract This study evaluates the immunogenicity of the HIV envelope protein (env) in mice presented either attached to γ-retroviral virus-like-particles (VLPs), associated with cell-derived microsomes or as solubilized recombinant protein (gp160). The magnitude and polyfunctionality of the cellular immune response was enhanced when delivering HIV env in the VLP or microsome form compared to recombinant gp160. Humoral responses measured by antibody titres were comparable across the groups and low levels of antibody neutralization were observed. Lastly, we identified stronger IgG2a class switching in the two particle-delivered antigen vaccinations modalities compared to recombinant gp160.